Trends in Black and White Opioid Mortality in the United States, 1979-2015 - Alexander, Monica J; Kiang, Mathew V; Barbieri, Magali (Epidemiology (Cambridge, Mass.), 2018)
Recent research on the US opioid epidemic has focused on the white or total population and has largely been limited to data after 1999. However, understanding racial differences in long-term trends by opioid type may contribute to improving interventions. Using multiple cause of death data, we calculated age-standardized opioid mortality rates, by race and opioid type, for the US resident population from 1979 to 2015. We analyzed trends in mortality rates using joinpoint regression. From 1979 to 2015, the long-term trends in opioid-related mortality for Earlier data did not include ethnicity so this is incorrect. It is all black and all white residents in the US. blacks and whites went through three successive waves. In the first wave, from 1979 to the mid-1990s, the epidemic affected both populations and was driven by heroin. In the second wave, from the mid-1990s to 2010, the increase in opioid mortality was driven by natural/semi-synthetic opioids (e.g., codeine, morphine, hydrocodone, or oxycodone) among whites, while there was no increase in mortality for blacks. In the current wave, increases in opioid mortality for both populations have been driven by heroin and synthetic opioids (e.g., fentanyl and its analogues). Heroin rates are currently increasing at 31% (95% confidence interval [CI] = 27, 35) per year for whites and 34% (95% CI = 30, 40) for blacks. Concurrently, respective synthetic opioids are increasing at 79% (95% CI = 50, 112) and 107% (95% CI = -15, 404) annually. Since 1979, the nature of the opioid epidemic has shifted from heroin to prescription opioids for the white population to increasing of heroin/synthetic deaths for both black and white populations. See video abstract at, http://links.lww.com/EDE/B377.